2013
DOI: 10.1038/bjc.2013.506
|View full text |Cite
|
Sign up to set email alerts
|

Hormone use and risk for lung cancer: a pooled analysis from the International Lung Cancer Consortium (ILCCO)

Abstract: Background:The association between oral contraceptive (OC) use, hormone replacement therapy (HRT) and lung cancer risk in women is still debated.Methods:We performed a pooled analysis of six case–control studies (1961 cases and 2609 controls) contributing to the International Lung Cancer Consortium. Potential associations were investigated with multivariable unconditional logistic regression and meta-analytic models. Multinomial logistic regressions were performed to investigate lung cancer risk across histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 49 publications
(101 reference statements)
2
49
1
1
Order By: Relevance
“…Some studies hypothesized that the association could be explained by long-term use of hormone replacement therapy prescribed to oophorectomized women 22, 44 . However, this explanation seems to be unlikely, as a previously published ILCCO pooled study demonstrated a protective effect of exogenous hormones, either oral contraceptives or hormone replacement therapy 45 .…”
Section: Discussionmentioning
confidence: 96%
“…Some studies hypothesized that the association could be explained by long-term use of hormone replacement therapy prescribed to oophorectomized women 22, 44 . However, this explanation seems to be unlikely, as a previously published ILCCO pooled study demonstrated a protective effect of exogenous hormones, either oral contraceptives or hormone replacement therapy 45 .…”
Section: Discussionmentioning
confidence: 96%
“…Our data also suggested that women with previous cancers had a higher risk for subsequent NSCLC than men. The effect of hormone exposure on lung cancer risk among women is not well defined but may be a contributing factor in the elevated risk of second primary lung cancer in women with previous malignancy, especially breast cancer 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen is considered to exhibit an important antitumor effect by reducing the proportion of matrix metalloproteinase-9/tissue inhibitor of metalloproteinase-1 (31). A multicenter study conducted by the International Lung Cancer Consortium (32) revealed that oral contraceptives, accepted hormone replacement therapy or a combination of estrogen and progesterone had been demonstrated to reduce the risk of lung cancer. In recent years, endocrine agents have gradually been used in the treatment of NSCLC.…”
Section: Overall Survival -------------------------------------------mentioning
confidence: 99%